The Effectiveness of Credit Rating Agency Monitoring: Evidence from Asset Securitizations - Bonsall, Samuel; Koharki, Kevin; Neamtiu, Monica (The Accounting Review, 2015)
ABSTRACT This study investigates how differences between the rating agencies' initial (at the date of debt issuance) and subsequent (post-issuance) monitoring incentives affect securitizing banks' rating accuracy. We hypothesize that the agencies have stronger incentives to monitor issuers when providing initial versus post-issuance ratings. We document that initial ratings are positively associated with off-balance sheet securitized assets and incrementally associated with on-balance sheet retained securities. However, subsequent ratings fail to capture current exposure to off-balance sheet securitizations. We also find that subsequent ratings reflect default risk less accurately than initial ratings. The subsequent ratings' responsiveness to default risk is worse when a bank has more off-balance sheet securitized assets. Collectively, our findings are consistent with lax post-issuance monitoring. They raise questions about the effectiveness of using ratings as an ongoing contracting mechanism and suggest that conclusions about rating accuracy could differ depending on whether researchers focus on initial versus post-issuance ratings.